Sostenibilidad económica y ambiental de la Producción mecanizada de Lombricompost empleando residuos vegetales - Morales Narvaez, Carlos Jair (2017)
The present thesis work aims to evaluate the economic and environmental sustainability of the mechanized production of lombricompost using vegetable waste.Economic sustainability profitability indicators were evaluated based ENPV and EIRR, for evaluating an economic rate of discount of 18% and 5-year period we were used. The ENPV measures the net absolute return provided by the project and EIRR for acceptance or rejection. If the ENPV is greater than 0, then we say that the mechanized production of lombricompost using vegetable waste is sustainable; if the EIRR is greater than the rate of economic discount 18% also say that the mechanized production of lombricompost using vegetable waste is sustainable, the greater will be the most EIRR profitability. The values of the profitability indicators obtained for mechanized production of lombricompost were: ENPV S/. 256,111.44 and EIRR 79%, where we can conclude based on these indicators mechanized production of lombricompost is economically sustainable. Environmental sustainability was assessed using the emergy method Company ombricompost, whose indicators evaluated and their values obtained are: rate of return Emergy 4.51, loading rate acclimates 0.40, renewability 55.3% and sustainability index 11.26, which we can see is sustainable, renewable and low environmental impact because it is therefore also environmentally feasible.